Supergene and exotic Cu mineralization occur during periods of landscape stability in the Centinela Mining District, Atacama Desert. (26th September 2017) - Riquelme, Rodrigo; Tapia, Miguel; Campos, Eduardo; Mpodozis, Constantino; Carretier, Sebastien; González, Rodrigo; Muñoz, Sebastian; Fernández‐Mort, Alberto; Sanchez, Caroline; Marquardt, Carlos
Abstract: The Centinela Mining District (CMD), Atacama Desert (northern Chile), includes several mid‐late Eocene porphyry Cu deposits that contains supergene mineralization and provides access to a record of gravel deposits that host syn‐sedimentary exotic Cu mineralized bodies. By studying these gravels, we reconstruct the unroofing history and constrain the geomorphological conditions that produced supergene and exotic Cu mineralization. We present an integrated study based on stratigraphic and sedimentological data, lithology clast counts, 40 Ar/ 39 Ar and U/Pb ages from interbedded tuff layers and U/Pb detrital zircon geochronology data. To relate the gravel deposition episodes to the timing of the supergene mineralization, we provide in‐situ and exotic supergene mineral ages (40Ar/39Ar and K‐Ar). Six gravel units were deposited between the mid‐Eocene and the mid‐Miocene. The Esperanza gravels were deposited concurrently with the emplacement of porphyry Cu deposits at depth. The subsequent Tesoro I, II and III and Atravesado gravels register the unroofing of these deposits, from the advanced argillic zone to the sericitic and prophylitic hypogene zones. The Arrieros gravels register landscape pediplanation, that is, denudational removal and wear of the landscape to base level on a relatively stable tectonic regime, occurring roughly contemporaneous with supergene activity. The supergene mineral ages of the CMD define a time span ( ca . 25–12 Ma) during which most of the supergene ages cluster in northern Chile. This time span corresponds with a period of warm and humid climate conditions in the southern hemisphere. We conclude that landscape pediplanation favours supergene mineralization and helps preserve the former supergene mineralized zones from significant erosion. Low erosion rates during pediplanation may constitute a necessary condition for the efficiency of the supergene processes in such semi‐arid climate.